PERAN PENDIDIKAN ISLAM INKLUSIF DI SEKOLAH DASAR DALAM MENJAGA TOLERANSI DI SUKU TENGGER - Moh Nadhif; Imam Alfafan (Al-Mudarris, 2025)
This study aim to describe, analyze, and provide an interpretation of the reasons why inclusive Islamic education is used as the first foothold in Sekolah Negeri 1 Tosari. This research uses a qualitative approach with a phenomenological type. The researcher went directly into the field, involving elements of school principals, teachers, and students as the main subjects. Data was collected through in-depth interviews, observations, and documentation. Data analysis is carried out qualitatively with an inductive approach through four activity flows: data collection, condensation, presentation, and verification. The results of this study show that inclusive Islamic education is used as the first foothold at Tosari Pasuruan State Elementary School 1 because it can encourage the creation of a harmonious educational environment, build inclusive spiritual and social awareness, and instill the value of tolerance through joint activities.